2020
DOI: 10.26717/bjstr.2020.30.004934
|View full text |Cite
|
Sign up to set email alerts
|

The Palestinian Terrestrial Vertebrate Fauna Preserved at The Biology Exhibitions of The Universities of The Gaza Strip

Abstract: Wild medicinal plants are an efficient source of anticancer agents. The widely distributed Launaea fragilis and Launaea nudicaulis in Egypt were investigated for their anti-proliferative activities against some cancer cell lines. Ethanol extracts of the two species were evaluated in vitro by Sulforhodamine B (SRB) assay on six cell lines; hepatocellular carcinoma (Hep G2), prostatic carcinoma (PC-3), colorectal carcinoma (HCT116), non-small cell lung carcinoma (H1299), breast adenocarcinoma (MCF7) and colon ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As far as the Palestinian Territories are concerned, special, deep works on cetaceans have never been found. All that is available are some marine reports or studies that cetaceans have been preserved or stuffed at the zoological exhibitions of the universities of the Gaza Strip (Abd Abd Rabou et al, 2020) . There are some non-in-depth studies that indicated the occurrence or beaching of cetacean species in the coastal waters of historic Palestine (Khalaf, 2008(Khalaf, , 2012(Khalaf, , 2019(Khalaf, and 2021a.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the Palestinian Territories are concerned, special, deep works on cetaceans have never been found. All that is available are some marine reports or studies that cetaceans have been preserved or stuffed at the zoological exhibitions of the universities of the Gaza Strip (Abd Abd Rabou et al, 2020) . There are some non-in-depth studies that indicated the occurrence or beaching of cetacean species in the coastal waters of historic Palestine (Khalaf, 2008(Khalaf, , 2012(Khalaf, , 2019(Khalaf, and 2021a.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these facts, Palestine plays as a stopover point for migratory bird fauna prior to continuing their annual migration from Eurasia to Africa and vice versa (UNEP, 2003). The Common Quail (Coturnix coturnix) is an important member of the Phasianidae family occurring in Palestine and hence the Gaza Strip (Abu Shammalah and Baha El-Din, 1999;Abd Rabou, 2005;2011a and b;2019a and b;2020a;Perlman and Meyrav, 2009;Khalilieh, 2016 andAbd Rabou et al, 2020). Several species of pheasants and partridges are extremely important to humans, with some of which have been widely used as game birds for hunting.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, numerous local studies recorded the occurrence of the bird in several environments of Palestine and confirmed its hunting for meat purposes (Euroconsult and IWACO, 1994;MedWetCoast, 2002;UNEP, 2003;Abd Rabou, 2005;2011a and b;2019a and b;Yassin et al, 2006 andAbd Rabou et al, 2007a). Abd Rabou (2020a) and Abd Rabou et al (2020) recorded many individuals of the bird preserved at the biology exhibitions of the local universities. More recently, Subaihi (2020) ensured the breeding of the Common Quail in the Gaza Strip as a new healthier and less expensive alternative for Gazans.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this widespread occurrence, no specimens of it were preserved at the biological exhibitions of local universities. Such a situation was attributed to the fact that the Cape Hare has become a rare mammal in the Gaza Strip, and all hunted specimens go for food purposes (Abd Rabou, 2020a andAbd Rabou et al, 2020). The Cape Hare is one of the biological threats facing the archaeological sites and buildings in the Gaza Strip because the burrows that it digs in the ground may cause the demolition of some ancient parts (Abd Rabou, 2019b).…”
mentioning
confidence: 99%